PENGARUH BIMBINGAN KELOMPOK TEKNIK ROLE PLAYING TERHADAP KEPERCAYAAN DIRI SISWA BROKEN HOME PADA SISWA KELAS X SMK PABAKU KEC. STABAT T.A. 2017/2018 - Sari Wardani Simarmata; Desi Arianti (Universitas Islam Negeri Sumatera Utara Medan, 2017)
The purpose of this research is: to know the influence of guidance group of roleplaying technique to the students' self confidence broken home on the students of class X SMK Pabaku District Stabat year lesson 2017/2018.This research was conducted at SMK Pabaku Kecamatan Stabat. The population in this study is the overall class X students who amounted to 31 students. While the sample in this study is broken home students who numbered 4 students. Based on the results of hypothesis testing is known that the calculation results can be rhitung at 0.95 while at rtabel at the level of 5% of 0.82. so concluded that the value of rhitung> rtabel so Ho in rejected, and Ha accepted that There is Influence Group Guidance Role Playing Techniques Against Self Confidence Students Broken Home In Students Class X SMK Pabaku Kec. Stabat Year 2017 / 2018. From the calculation of t test to determine the significance of the influence between guidance group of role playing techniques with student self-confidence, has obtained the value with the crude figures of t test formula obtained counted 6.3. Once it is known that the value of t count of 6.3. Can also be seen on the test ttabeld with sample 6 at 5% significant indicate 2.8, so the value of rhitung> rtabel or 2,9> 2,78. so it can be concluded that there is a significant influence between the guidance of the group of role playing techniques to the students' self-confidence broken home on the students of class X SMK Pabaku Kec. Stabat year 2017/2018. Keywords: Group Conseling, Role Playing, Self-Confidence, Broken Home